Becoming part of the gang? Established and nonestablished populist parties and the role of external efficacy - Werner Krause; Aiko Wagner (Party Politics, 2021)
In this article, we examine the extent to which the influence of external efficacy on support for populist parties is conditional on the degree to which a populist party is an established player in a given party system. We do so using a two-step regression approach that allows us to investigate the varying effect of external efficacy in a multilevel setting. Making use of data on 23 European Union member states, we empirically demonstrate that the nature of support for populists varies depending on the extent to which these parties are established actors in their national party systems. This is true for Western and Eastern European populist parties. These findings make an important contribution to the broader literature on the success and survival of populist parties. They indicate that these parties do not keep up their image as radical opponents of the national political establishment the more they become electorally successful and join government coalitions.
Keywords: 330; electoral behavior; established parties; external efficacy; populist parties